2020
DOI: 10.1108/ijoem-04-2018-0191
|View full text |Cite
|
Sign up to set email alerts
|

FDI determinants: dynamic extreme bounds analysis

Abstract: PurposeThe aim of this paper is to develop a new analysis method, named dynamic extreme bounds analysis (DEBA), and to determine decisive determinants of foreign direct investment (FDI) by using this new method.Design/methodology/approachIn econometrics, the extreme bounds analysis (EBA) method is a convincing way of examining the strength of independent variables. However, the results obtained when using the EBA method contain little information, since each variable is only either strong or fragile, and some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In general, most of the previous studies which have focused on analyzing the association between FDI and macroeconomic factors have found that FDI significantly influences the economic activities in both developed and emerging market economies (Bhasin and Kapoor, 2020; Pham and Wongsurawat, 2020; Coussi et al , 2018; Wang and Li, 2018; Park and Roh, 2019). Over the years, foreign investment has grown significantly in several developing economies and has become a key constituent of the local system.…”
Section: Introductionmentioning
confidence: 99%
“…In general, most of the previous studies which have focused on analyzing the association between FDI and macroeconomic factors have found that FDI significantly influences the economic activities in both developed and emerging market economies (Bhasin and Kapoor, 2020; Pham and Wongsurawat, 2020; Coussi et al , 2018; Wang and Li, 2018; Park and Roh, 2019). Over the years, foreign investment has grown significantly in several developing economies and has become a key constituent of the local system.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some country-specific studies have identified potential determinants of FDI such as trade openness [ 76 – 80 ] market sizes [ 77 81 ], labour costs, human capital [ 77 , 80 ], infrastructure availability [ 77 , 79 , 80 ], industry value added, government consumption, telephone mainlines per 100 of population, financial development, service value-added, inflation and commercial energy use per capita. Moreover, expected years of schooling, political stability [ 76 ], exchange rates, tax rates, tax depreciation, tax holidays, trade barriers, gross domestic investment, gross capital formation, technology gap, economic freedom, research and development, and corruption [ 77 ] are considered.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, some country-specific studies have identified potential determinants of FDI such as trade openness [ 76 – 80 ] market sizes [ 77 81 ], labour costs, human capital [ 77 , 80 ], infrastructure availability [ 77 , 79 , 80 ], industry value added, government consumption, telephone mainlines per 100 of population, financial development, service value-added, inflation and commercial energy use per capita. Moreover, expected years of schooling, political stability [ 76 ], exchange rates, tax rates, tax depreciation, tax holidays, trade barriers, gross domestic investment, gross capital formation, technology gap, economic freedom, research and development, and corruption [ 77 ] are considered. Further, these factors are considered key determinants: economic risk rating, financial risk rating, political risk rating, commodity price index, world stock market index, gross fixed capital formation [ 78 ], GDP growth, macro-economic stability, school enrollment rate [ 79 ], growth prospects and positive country conditions, government finance, rate of return on investment, policy measures [ 79 ], economic potential, labour market characteristics, technological progress, labour regulation, competitiveness and eligibility for Cohesion Fund [ 81 ].…”
Section: Literature Reviewmentioning
confidence: 99%